Does chronic kidney disease affect implant survival after primary hip and knee arthroplasty?. (1st April 2021) - Jämsä, Pyry; Reito, Aleksi; Oksala, Niku; Eskelinen, Antti; Jämsen, Esa
Abstract : Aims: To investigate whether chronic kidney disease (CKD) is associated with the risk of all-cause revision or revision due to a periprosthetic joint infection (PJI) after primary hip or knee arthroplasty. Methods: This retrospective cohort study comprised 18, 979 consecutive hip and knee arthroplasties from a single high-volume academic hospital. At a median of 5.6 years (interquartile range (IQR) 3.5 to 8.1), all deaths and revisions were counted. To overcome the competing risk of death, competing risk analysis using the cumulative incidence function (CIF) was applied to analyze the association between different stages of CKD and revisions. Confounding factors such as diabetes and BMI were considered using either a stratified CIF or the Fine and Gray model. Results: There were 2, 111 deaths (11.1%) and 677 revisions (3.6%) during the follow-up period. PJI was the reason for revision in 162 cases (0.9%). For hip arthroplasty, 3.5% of patients with CKD stage 1 (i.e. normal kidney function, NKF), 3.8% with CKD stage 2, 4.2% with CKD stage 3, and 0% with CKD stage 4 to 5 had undergone revision within eight years. For knee arthroplasty, 4.7% with NKF, 2.7% with CKD stage 2, 2.4% with CKD stage 3, and 7% of CKD stage 4 to 5 had had undergone revision. With the exception of knee arthroplasty patients in whom normal kidney function was associated with a greater probability of all-cause revision, there were no major differences in the rates of all-cause revisions or revisions due to PJIs between different CKD stages. The results remained unchanged when diabetes and BMI were considered. Conclusion: We found no strong evidence that CKD was associated with an increased risk of all-cause or PJI-related revision. Selection bias probably explains the increased amount of all-cause revision operations in knee arthroplasty patients with normal kidney function. The effect of stage 4 to 5 CKD was difficult to evaluate because of the small number of patients. Cite this article: Bone Joint J  2021;103-B(4):689–695.